Thinking Globally, Acting Locally: Harnessing the Immune System to Deal with Recalcitrant Pathogens - Michael W. Russell (American Society for Microbiology, 2015)
ABSTRACT Traditional approaches to harnessing the immune system to confront infectious diseases depend on vaccines, which have generally proven highly effective, but for many infections these either are not available or are of limited effectiveness. Although antibiotic therapy has been extremely successful in reducing the burden of bacterial disease, the emergence of resistance among several important pathogens threatens to undermine this accomplishment, and despite some successes chemotherapeutic treatments for viral, fungal, and parasitic infections are more limited. Understanding the mechanisms whereby pathogens manipulate the immune system to favor their survival, or exploit weaknesses in host immunity, can lead to novel approaches for the treatment of infections by redirecting host immune responses against the pathogen. Such treatments may be most effectively applied at the mucosal locations which are frequently the sites of initial infection and may also suggest new approaches for vaccine development.